Proton superfluidity and charge radii in proton-rich calcium isotopes - Miller, A. J.; Minamisono, K.; Klose, A.; Garand, D.; Kujawa, C.; Lantis, J. D.; Liu, Y.; Maaß, B.; Mantica, P. F.; Nazarewicz, W.; Nörtershäuser, W.; Pineda, S. V.; et al. (Nature Physics, 2019)
One of the most important global properties of the atomic nucleus is its size. Experimentally determined nuclear charge radii carry unique information on the nuclear force and complex dynamics of protons and neutrons moving inside the nucleus. The intricate behaviour of charge radii along the chain of Ca isotopes, including the unexpectedly large charge radius of neutron-rich 52 Ca, poses a daunting challenge for nuclear theory 1 . Here we present the measurements of the charge radii of proton-rich isotopes 36,37,38 Ca, whose properties are impacted by the interplay between nuclear superfluidity and weak binding. Calculations carried out within nuclear density functional theory show that the combination of a novel interaction 2 and a state-of-the-art theoretical method can successfully explain the behaviour of charge radii from the lightest to the heaviest Ca isotopes. Through this model, we show how the new data on 36,37,38 Ca elucidate the nature of nucleonic pairing in weakly bound proton-rich isotopes.
CRIS-Team Scopus Importer:2019-05-14